Toxicity and disruption of quorum sensing in Aliivibrio fisheri by environmental chemicals: Impacts of selected contaminants and microplastics - François Gagné (Journal of Xenobiotics, 2017)
The purpose of this study was to examine the effects of dissolved and particulate compounds on quorum sensing in the marine luminescent bacterium Aliivibrio fisheri. Bacteria were exposed to increasing concentrations of CuSO4 (Cu2+), gadolinium chloride (Gd3+), 20-nm silver nanoparticles (nanoAg) and 1-3 μm microplastic polyethylene beads for 250 min. During this period, luminescence measurements were taken at 5-min intervals. Toxicity was first examined by measuring luminescence output at 5-min and 30-min incubation time. Based on the effective concentration that decreases luminescence by 20% (EC20), the compounds were toxic at the following concentrations in decreasing toxicity: Cu2+ (3.2 mg/L) < nanoAg (3.4 mg/L, reported) < Gd3+ (34 mg/L) < microplastics (2.6 g/L). The data revealed that luminescence changed non-linearly over time. In control bacteria, luminescence changed at eight specific major frequencies between 0.04 and 0.27 cycle/min after Fourier transformation of time-dependent luminescence data. The addition of dissolved Cu2+ and Gd3+ eliminated the amplitude changes at these frequencies in a concentration-dependent manner, indicating loss of quorum sensing between bacteria at concentrations below EC20. In the presence of nanoAg and microplastic beads, the decreases in amplitudes were modest but compressed the luminescence profiles, with shorter frequencies appearing at concentrations well below EC20. Thus, loss of communication between bacteria occurs at non-toxic concentrations. In addition, with exposure to a mixture of the above compounds at concentrations that do not produce effects for Gd3+, nanoAg and microplastics, Cu2+ toxicity was significantly enhanced, suggesting synergy. This study revealed for the first time that small microplastic particles and nanoparticles can disrupt quorum sensing in marine bacteria.